Chemotaxonomic patterns of vegetation and soils along altitudinal transects of the Bale Mountains, Ethiopia, and implications for paleovegetation reconstructions – Part II: lignin-derived phenols and leaf-wax-derived n-alkanes - B. Lemma; B. Lemma; B. Mekonnen; B. Mekonnen; B. Glaser; W. Zech; S. Nemomissa; T. Bekele; L. Bittner; M. Zech; M. Zech (Eiszeitalter und Gegenwart, 2019)
Erica is a dominant vegetation type in many sub-afroalpine ecosystems, such as the Bale Mountains in Ethiopia. However, the past extent of Erica is not well known and climate versus anthropogenic influence on altitudinal shifts are difficult to assign unambiguously, especially during the Holocene. The main objective of the present study is to chemotaxonomically characterize the dominant plant species occurring in the Bale Mountains using lignin phenols and n-alkane biomarkers and to examine the potential of those biomarkers for reconstructing vegetation history. Fresh plant material, organic layer and mineral topsoil samples were collected along a northeastern and a southwestern altitudinal transect (4134–3870 and 4377–2550 m a.s.l., respectively). Lignin-derived vanillyl, syringyl and cinnamyl phenols were analyzed using the cupric oxide oxidation method. Leaf-wax-derived n-alkanes were extracted and purified using Soxhlet and aminopropyl columns. Individual lignin phenols and n-alkanes were separated by gas-chromatography and detected by mass spectrometry and flame ionization detection, respectively. We found that the relative contributions of vanillyl, syringyl and cinnamyl phenols allow us to chemotaxonomically distinguish contemporary plant species of the Bale Mountains. Erica in particular is characterized by relatively high cinnamyl contributions of >40 %. However, litter degradation strongly decreases the lignin phenol concentrations and completely changes the lignin phenol patterns. Relative cinnamyl contributions in soils under Erica were <40 %, while soils that developed under Poaceae (Festuca abyssinica) exhibited relative cinnamyl contributions of >40 %. Similarly, long-chain n-alkanes extracted from the leaf waxes allowed for differentiation between Erica versus Festuca abyssinica and Alchemilla, based on lower C31 ∕ C29 ratios in Erica. However, this characteristic plant pattern was also lost due to degradation in the respective O layers and Ah horizons. In conclusion, although in modern-day plant samples a chemotaxonomic differentiation is possible, soil degradation processes seem to render the proxies unusable for the reconstruction of the past extent of Erica on the Sanetti Plateau, Bale Mountains, Ethiopia. This finding is of high relevance beyond our case study.